Diagnostic value of Kaiser score combined with breast vascular assessment from breast MRI for the characterization of breast lesions - Zhou, Xin-zhu; Liu, Lian-hua; He, Shuang; Yao, Hui-fang; Chen, Li-ping; Deng, Chen; Li, Shuang-Ling; Zhang, Xiao-yong; Lai, Hua (Frontiers in Oncology, 2023)
Objectives. Kaiser scoring system for breast magnetic resonance imaging (bMRI) is a clinical decision-making tool in diagnosing breast lesions. However, the Kaiser score (KS) did not include the evaluation of breast vascularity. Therefore, this study aimed to using of KS combined with breast vascular assessment，defined as KS*, and investigate the effectiveness of KS* in differentiating benign from malignant breast lesions. Methods. This retrospective study included 223 patients with suspicious breast lesions and pathologically verified results. The histopathological diagnostic criteria were according to the fifth edition of WHO classification of breast tumors. The KS* was obtained after joint evaluation combing the original KS and breast vasculature assessment. The receiver operating characteristic (ROC) curve was used for comparing differences in the diagnostic performance between KS* and KS, and the area under the receiver operating characteristic (AUC) was compared. Results. There were 119 (53.4%) benign and 104 (46.6%) malignant lesions in total. The overall sensitivity, specificity, and accuracy of increased ipsilateral breast vascularity were 69.2%, 76.5%, and 73.1%, respectively. The overall sensitivity, specificity, and accuracy of AVS were 82.7%, 76.5%, and 79.4%, respectively. For all lesions included, the AUC of KS* was greater than that of KS (0.877 vs. 0.858, P=0.016). The largest difference between AUC was observed in the non-mass subgroup (0.793 vs. 0.725, P=0.029). Conclusions. Ipsilateral increased breast vascularity and positive AVS sign were significantly associated with malignancy. KS combined with breast vascular assessment can effectively improve the diagnostic ability of KS for breast lesions, especially for non-mass lesions.